Temperature variation caused by high-intensity LED curing lights in bovine dentin - Mollica, Fernanda Brandao; Silva, Melissa Aline; De Araujo, Maria Amelia Maximo; Lima Huhtala, Maria Filomena R.; Balducci, Ivan (My University, 2009)
This study sought to evaluate the temperature variations in bovine dentin when cured with high-intensity LED appliances and quartz-tungsten-halogen (QTH) appliances. Forty-five slices of bovine dentin (0.7 mm thick) were divided into three groups. Temperature variations were measured during polymerization of the adhesive (10 seconds), during polymerization of the resin composite (40 seconds), and 24 hours after the resin composite polymerization. The data were submitted to the ANOVA repeated measures test, which showed a statistically significant difference in the interaction factor (p = 0.0001). Tukey's test (p = 5%) revealed that the SmartLite PS LED appliance caused a significantly higher temperature increase than the other appliances following polymerization of the adhesive, that both LED appliances produced significantly greater temperature increases than the QTH curing light during polymerization of the resin composite, and that the SmartLite PS produced the greatest temperature increase after 24 hours.